Cannibalism and protective behavior of eggs in Arctic charr (Salvelinus alpinus) - Frye, Marilena; Egeland, Torvald Blikra; Nordeide, Jarle Tryti; Folstad, Ivar (Ecology and Evolution, 2021)
From video recordings of spawning events, we quantified protective and cannibalistic behavior of Arctic charr occurring immediately after spawning. The number of fish cannibalizing on stray eggs was examined regarding (a) whether more than one male shed milt during the spawning event, that is, whether sperm competition occurred, (b) whether the sperm competition included few or many males, that is, the intensity of sperm competition, and (c) the density of fish at the spawning site. Response behavior toward egg cannibalism was also examined among females and dominant males in order to determine any parental investment toward protecting the eggs after spawning. Cannibalistic behavior was seen in almost 50% of the spawnings, and the multiple spawning events showed the highest numbers of fish cannibalizing on eggs. Both the number of males releasing milt and the number of fish approaching the spawning site were positively correlated with egg cannibalism. Sperm competition was, however, not a prerequisite for egg cannibalism. Although we also observed partial filial cannibalism, protective behavior of eggs was seen both among dominant males and females, suggesting that charr actually conduct parental care.